PENGARUH SENIORITAS DAN PRESTASI KERJA TERHADAP PROMOSI JABATAN PADA KARYAWAN - Purwaningsih, Amalia; Magdalena, Betty (Jurnal Bisnis Darmajaya, 2017)
Problems that occurred in PT. Bank Panin Bandar Lampung is less effective office promotion system and can be seen on the assessment of employee results in the period 2016 is still the low responsibility of employees to their duties. This study aims to determine whether there is influence seniority on a promotion of positions, to determine whether there is an influence of work performance on promotion positions, to determine whether there are influence seniority and job performance on promotion positions. The object of research taken is PT. Bank Panin Bandar Lampung. This type of research uses a quantitative approach with the assosiative method. Population in this research is all employees of PT. Bank Panin Bandar Lampung as many as 149 people. The sample in this research is as much as 99 respondents. Sempel sampling method is by using probability sampling by using technique stratified random sampling and simple random sampling. Methods of data analysis using multiple linear regression analysis, t test, and F test. The results showed that the Seniority and Achievement of Work have a significant effect on Promotion Position on Employees PT. Bank Panin Bandar Lampung.Keywords â Seniority, Job Performance, Promotion, Learning theory, Panin Bank